Developing short stories in teaching both physics content and reading skills - Minerales, Mark Albert A.; Malayao Jr., Sotero O.; Salic-Hairulla, Monera A.; Sayson, Noel Lito B.; Magallanes, Jingle B. (Intelektual Pustaka Media Utama, 2025)
The Philippine basic education continually languishes at the bottom in programme for international student assessment (PISA) and low achievement in national achievement test (NAT) thus the need for creative learning supplementation is a must. This study attempted to use reading as platform to engender science learning thereby hitting two goals in one intervention. Six contextualized science-infused reading materials were developed corresponding to the six topics in grade 7 science and utilizing the analysis, design, development, implementation, and evaluation (ADDIE) model as the developmental framework. The material passed the department of education criteria in terms of language evaluation and format while the content was evaluated by field experts. The material has an average lexical density of 51.45 and Flesch-Kincaid grade level of 7.80. The pandemic limited the target respondents to 54. Initial results showed that the material can possibly contribute to science learning based on the medium normalized gain. In terms of intrinsic motivation, all areas were rated high indicating that the users are well-motivated in using the reading material. The material also points to its potential to positively impact reading fluency. It is recommended that similar material be developed for all physics content in all levels from grade 3 to grade 10 and possibly be replicated in other science area.